(untitled) (Studia austriaca, 2024)
This paper delves into autobiographical texts, uncovering thematic and narrative parallels, with a keen focus on the depiction of humiliations in Das rauhe Leben [The Rough Life] by Alfons Petzold and Ein Mann seiner Klasse [A Man of his Class] by Christian Baron. It posits humiliation as both excluding and order-establishing, yet also catalyzing resistance to societal exclusion. Following a theoretical examination of humiliation, the study scrutinizes how it shapes the autobiographical narratives, analyzing narrative techniques, its impact on plot and character, spatial significance, and associated discourses.